Use of the wearable cardioverter-defibrillator (WCD) and WCD-based remote rhythm monitoring in a real-life patient cohort - Zylla, Maura Magdalena; Hillmann, Henrike Aenne Katrin; Proctor, Tanja; Kieser, Meinhard; Scholz, Eberhard P.; Zitron, Edgar; Katus, Hugo; Thomas, Dierk (Heart and vessels, 2018)
The wearable cardioverter-defibrillator (WCD) was introduced to provide protection from sudden cardiac death (SCD) in patients with transiently elevated risk or during ongoing risk stratification. Benefits and clinical characteristics of routine WCD use remain to be assessed in larger patient populations. This study aims to identify determinants of WCD compliance, therapies, and inappropriate alarms in a real-life cohort. A total of 106 cases (68.9% male) were included between 11/2010 and 04/2016. WCD therapies, automatically recorded arrhythmia episodes, inappropriate WCD alarms, patient compliance, and outcome after WCD prescription were analyzed. Median duration of WCD use was 58.5 days. Average daily wearing time was 22.7 h. Compliance was reduced in patients ≤ 50 years. Three patients received WCD therapies (2.8%). In one case ventricular fibrillation (VF) was appropriately terminated with the first shock. Two patients received inappropriate WCD therapies due to WCD algorithm activation during ventricular pacemaker stimulation. One patient died of asystole while carrying a WCD (0.9%). Additional arrhythmias detected comprised self-terminating sustained ventricular tachycardia (VT; 2.8%), non-sustained VT (2.8%), and supraventricular arrhythmias (5.7%). Inappropriate WCD alarms due to over-/undersensing occurred in 77/106 patients (72.6%), of which 41 (38.7%) experienced ≥ 10 inappropriate WCD alarms during the prescription period. Thirteen patients (12.3%) displayed a mean of > 1 inappropriate alarms/day. WCD use was associated with high compliance and provided protection from VT/VF-related SCD. The majority of patients experienced inappropriate WCD alarms. Alterations in QRS morphology during pacemaker stimulation require consideration in WCD programming to prevent inappropriate alarms.